PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 010 RANTAU PANJANG KIRI KECAMATAN KUBU KABUPATEN ROKAN HILIR - Amriwati, Amriwati; Noviana, Eddy; Lazim. N, Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the low learning outcomes IPA of fourth grade on Elementary School 010 Rantau Panjang Kiri Kecamatan Kubu with an average score of 61.05 class, the KKM is 70. Where the 20 students who reach the KKM is 7 students (35%) while not complete is 13 students (65%). This research aims to improve learning outcomes IPA of fourth grade on Elementary School 010 Rantau Panjang Kiri Kecamatan Kubu on 2014/2015 school year with the implementation of cooperative learning model NHT. At the first meeting of the first cycle of activity with the percentage of 54.16% teachers with enough category. While at the second meeting of the percentage of the activities of teachers has risen 75.00% in both categories. While in the second cycle of the first meeting and the second percentage teacher activity reached 95.83% with very good category. At the first meeting of the first cycle of activity with the percentage of 54.16% students with enough categories, while the second meeting increased to 66.66%. Either category. While the first meeting of the second cycle of the percentage of student activity is 91.66% with very good categories and the second meeting increased to 95.83% with very good category. It can be concluded that the implementation of cooperative learning model NHT improve learning outcomes IPA of fourth grade on Elementary School 010 Rantau Panjang Kiri Kecamatan Kubu.Keywords: numbered head together and IPA learning outcomes